Akuntansi Syariah Untuk Pembiayaan Murabahah, Mudharabah Serta Kesesuaian Dengan PSAK Syariah No 102 Dan 105 Pada KSPPS BMT NU Jombang - Nurdiwaty, Diah; Widiawati, Hestin Sri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
This research is motivated by the financing of Murabahah and Mudharabah being the dominant products chosen by customers in the development of micro business, and the implementation of Murabahah and Mudharabah financing is not yet in accordance with Sharia PSAK No. 102 and 105. The researcher will see how the suitability of Murabahah financing treatment, Mudharabah in KSPPS BMT NU Jombang with financial accounting standards (PSAK) No.102 and 105. This study uses a qualitative method descriptive approach. In collecting research data using primary data in the form of interviews and observations, secondary data in the form of documentation presented by KSPPS BMT NU Jombang. Data collection techniques in this study use library research (library reserch), field research (field research). The analysis technique used in this study was to adjust the practice of KSPPS BMT NU with PSAK, then the results obtained from the analysis sought the cause. The conclusion of this study shows the application of Islamic accounting in the financing of Murabahah and Mudharabah in KSPSS BMT NU Jombang in accordance with the SOP in KSPPS BMT NU Jombang. Whereas the suitability of the treatment of Islamic accounting financing for Murabahah financing, Mudharabah against PSAK No. 102 and 105 are not yet appropriate. Incompatibility with the recognition and measurement of assets and advances for Murabahah financing.